Corporate environmental responsibility, motivational factors, and effectiveness: A case of Indian iron and steel industry. Issue 2 (19th November 2019) - Haider, Salman; Adil, Masudul Hasan; Mishra, Prajna Paramita
Abstract : This study provides an understanding of motivational factors that lead to the adoption of an environmental management system (EMS) from the perspective of resource‐based view theory. Further, the role of EMS has been examined to reduce energy intensity by estimating the average treatment effect. Therefore, different logistic regression has been estimated to find out major motivational factors. Results from the logit model validate the role of firm's size, age, and ownership in motivating firms to adopt an EMS whereas regulatory pressure does not influence the firm's adoption of EMS. Furthermore, negative average treatment effect shows the effectiveness of certification in reducing energy intensity. The comparative analysis of sustainability report indicates that TATA Steel outperforms in terms of carbon emission intensity as compared with Steel Authority of Indian Limited, Jindal power and steel limited, JSW Steel, and average Indian firms. Nonetheless, top Indian steel companies are far behind the global best practices in terms of energy, water, emission, and effluent performance indicators.